PENGARUH TRANSPARANSI ANGGARAN, AKUNTABILITAS KEUANGAN, DAN PENGGUNAAN ALOKASI DANA DESA TERHADAP KEPERCAYAAN MASYARAKAT DI KECAMATAN COLOMADU, KABUPATEN KARANGANYAR, JAWA TENGAH - Eka Setya Ningrum; LMS. Kristiyanti; Indra Lila Kusuma (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
Villages are the smallest administrative units that play a strategic role in national development, but there are still problems in the management of village funds that have led to low public trust. This study aims to analyze the influence of budget transparency, financial accountability, and the use of village fund allocations on public trust. This study employs a quantitative method using a survey approach and the distribution of questionnaires to 125 respondents in Colomadu District. The results indicate that budget transparency does not significantly influence public trust, while financial accountability and the use of village fund allocations have a positive and significant impact on public trust. Based on these findings, to enhance public trust, it is necessary to strengthen accountability practices and the effective use of village fund allocations, although budget transparency has not yet become a decisive factor in building local public trust